ANALISIS KEMAMPUAN KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA PT. PEGADAIAN PALANGKA RAYA - Robert Fransiska (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
Human resources will determine on the success of company activity implementation. There is an increasing urgent need for companies to obtain, develop and maintain qualified human resources in accordance with always changing environmental dynamic. This research aims to (1). To determine the influences of communication and leadership ability on the effectiveness of employees at PT. Pegadaian (Persero) Branch of Palangka Raya (2).To find out the variable with the most dominant influence on employee effectiveness at PT. Pegadaian (Persero) Branch of Palalangka Raya. This research was conducted at the Office of PT. Pegadaian Branch of Palangka Raya on A. Yani Street as the research objects are the employees who work at PT. Pegadaian Branch of Palangkaraya. Based on the partial test conducted on the variables included in the analysis model, it can be seen that both research variables, namely Communication variable (X1) of 0.377, and organizational culture (X2) of 0.363, which simultaneously have influence and significance on the effectiveness of employee working at PT. Pegadaian Branch of Palangkaraya. Similarly, if seen partially, it is known that both variables have positive and significant influences. The communication ability performed by the employees serves as the most dominant variable on the work effectiveness of employees of PT. Pegadaian Branch of Palangkaraya which could be seen from the amount of influence namely by 37.7%.